EMPIRICAL INVESTIGATION OF STYLE INTERACTIONS IN THE LINGUISTIC IMAGE STRUCTURE - Bilyk, Tatyana Nikolaevna (Psychological Prospects Journal, 2013)
The article analyzes the theoretical analysis of the speech style, in which the psychological component of the speech image is realized. The results of the empirical study of the peculiarities of the structure of the intercommunication of the speech style with other styles of speech image and psychological peculiarities of the personality are revealed.